2022
DOI: 10.48550/arxiv.2201.07831
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reduced models for ETG transport in the pedestal

David R. Hatch,
Craig Michoski,
Dongyang Kuang
et al.

Abstract: This paper reports on the development of reduced models for electron temperature gradient (ETG) driven transport in the pedestal. Model development is enabled by a set of 61 nonlinear gyrokinetic simulations with input parameters taken from the pedestals in a broad range of experimental scenarios. The simulation data has been consolidated in a new database for gyrokinetic simulation data, the Multiscale Gyrokinetic Database (MGKDB), facilitating the analysis. The modeling approach may be considered a generaliz… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…We have shown that retaining k y ρ i ∼ 1 ETG modes is crucial to capture correctly the k y ρ e ∼ 1 electron heat flux. This is relevant for tokamak turbulence modeling [52,[110][111][112][113][114][115] that aims to predict experimental fluxes accurately. While this result is not the first to show k y ρ i ∼ 1 turbulence suppressing k y ρ e ∼ 1 turbulence [21,23,24,116], it is the first to show ETG turbulence at k y ρ i ∼ 1 suppressing ETG turbulence and transport at k y ρ e ∼ 1.…”
Section: Multiscale Etg-etg Interactionsmentioning
confidence: 99%
“…We have shown that retaining k y ρ i ∼ 1 ETG modes is crucial to capture correctly the k y ρ e ∼ 1 electron heat flux. This is relevant for tokamak turbulence modeling [52,[110][111][112][113][114][115] that aims to predict experimental fluxes accurately. While this result is not the first to show k y ρ i ∼ 1 turbulence suppressing k y ρ e ∼ 1 turbulence [21,23,24,116], it is the first to show ETG turbulence at k y ρ i ∼ 1 suppressing ETG turbulence and transport at k y ρ e ∼ 1.…”
Section: Multiscale Etg-etg Interactionsmentioning
confidence: 99%
“…We have shown that retaining k y ρ i ∼ 1 ETG modes is crucial to capture correctly the k y ρ e ∼ 1 electron heat flux. This is relevant for tokamak turbulence modeling [52,[106][107][108][109][110][111] that aims to predict experimental fluxes accurately. While this result is not the first to show k y ρ i ∼ 1 turbulence suppressing k y ρ e ∼ 1 turbulence [21,23,24,112], it is the first to show ETG turbulence at k y ρ i ∼ 1 suppressing ETG turbulence and transport at k y ρ e ∼ 1.…”
Section: Multiscale Etg-etg Interactionsmentioning
confidence: 99%